ATP binding cassette transporter gene expression in rat liver progenitor cells. Issue 7 (1st July 2003) - Ros, J E; Roskams, T A D; Geuken, M; Havinga, R; Splinter, P L; Petersen, B E; LaRusso, N F; van der Kolk, D M; Kuipers, F; Faber, K N; Müller, M; Jansen, P L M
Abstract : Background and aim: Liver regeneration after severe liver damage depends in part on proliferation and differentiation of hepatic progenitor cells (HPCs). Under these conditions they must be able to withstand the toxic milieu of the damaged liver. ATP binding cassette (ABC) transporters are cytoprotective efflux pumps that may contribute to the preservation of these cells. The aim of this study was to determine the ABC transporter phenotype of HPCs. Methods: HPC activation was studied in rats treated with 2- acetylaminofluorene (2-AAF) followed by partial hepatectomy (PHx). ABC transporter gene expression was determined by real time detection reverse transcription-polymerase chain reaction in isolated HPCs, hepatocytes, cholangiocytes, and cultured progenitor cell-like RLF ϕ 13 cells and by immunohistochemistry of total liver samples. ABC transporter efflux activity was studied in RLF ϕ 13 cells by flow cytometry. Results: 2-AAF/PHx treated animals showed increased hepatic mRNA levels of the genes encoding multidrug resistance proteins Mdr1b, Mrp1, and Mrp3 . Immunohistochemistry demonstrated expression of Mrp1 and Mrp3 proteins in periportal progenitor cells and of the Mdr1b protein in periportal hepatocytes. Freshly isolated Thy-1 positive cells and cultured RLF ϕ 13 progenitor cells highly expressed Mrp1 and Mrp3 mRNA while the hepatocyte specific transporters Mdr2, Bsep, Mrp2, and Mrp6 were only minimally expressed. Blocking Mrp activity by MK-571 resulted in accumulation of the Mrp specific substrate carboxyfluorescein in RLF ϕ 13 cells. Conclusion: HPCs express high levels of active Mrp1 and Mrp3. These may have a cytoprotective role in conditions of severe hepatotoxicity.